Glial Lipid Droplets and ROS Induced by Mitochondrial Defects Promote Neurodegeneration - Liu, Lucy; Zhang, Ke; Sandoval, Hector; Yamamoto, Shinya; Jaiswal, Manish; Sanz, Elisenda; Li, Zhihong; Hui, Jessica; Graham, Brett H.; Quintana, Albert; Bellen, Hugo J. (Cell, 2015)
Reactive oxygen species (ROS) and mitochondrial defects in neurons are implicated in neurodegenerative disease. Here, we find that a key consequence of ROS and neuronal mitochondrial dysfunction is the accumulation of lipid droplets (LD) in glia. In Drosophila, ROS triggers c-Jun-N-terminal Kinase (JNK) and Sterol Regulatory Element Binding Protein (SREBP) activity in neurons leading to LD accumulation in glia prior to or at the onset of neurodegeneration. The accumulated lipids are peroxidated in the presence of ROS. Reducing LD accumulation in glia and lipid peroxidation via targeted lipase overexpression and/or lowering ROS significantly delays the onset of neurodegeneration. Furthermore, a similar pathway leads to glial LD accumulation in Ndufs4 mutant mice with neuronal mitochondrial defects, suggesting that LD accumulation following mitochondrial dysfunction is an evolutionarily conserved phenomenon, and represents an early, transient indicator and promoter of neurodegenerative disease. [Display omitted] •Lipid droplets (LD) are transient and occur prior to neurodegeneration in flies and mice•LD are present in glia and induced by neuronal increase of ROS, JNK, and SREBP•Reduction of ROS by antioxidants, lipases, or lower JNK or SREBP, delay degeneration•Neurodegeneration in mice with ROS/lipid droplets can be delayed with antioxidants Lipid droplet accumulation in glial cells, driven by mitochondrial defects and ROS in neurons, contribute to neurodegeneration in a Drosophila model, with evidence of a conserved mechanism in mice.